Feasibility of a Mobile Messaging-Enhanced Brief Intervention for High Risk Heavy Drinking MSM: A Pre-Pilot Study. Issue 1 (2nd January 2020) - Chavez, Kathryn; Palfai, Tibor P.
ABSTRACT: The purpose of this project was to assess the feasibility of an in-person session + mobile messaging intervention approach to reduce heavy drinking and condomless anal intercourse among heavy drinking men who have sex with men at high risk for HIV. Participant ( n = 8) engagement rates, retention and satisfaction ratings were used to measure feasibility and acceptability of the 4-week intervention. Paired t-tests were used to assess additional secondary outcomes. Results support the feasibility and acceptability of this novel treatment approach among this population. Pre-post intervention effect sizes on alcohol, sex risk and process variable secondary outcomes are discussed.